2015
DOI: 10.1002/wnan.1356
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐motivated gene delivery for ophthalmic application

Abstract: Ophthalmic gene therapy is an intellectual and intentional manipulation of desired gene expression into the specific cells of an eye for the treatment of ophthalmic (ocular) genetic dystrophies and pathological conditions. Exogenous nucleic acids such as DNA, small interfering RNA (siRNA), micro RNA (miRNA), etc., are used for the purpose of managing expression of the desired therapeutic proteins in ocular tissues. The delivery of unprotected nucleic acids into the cells is limited due to exogenous and endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
(164 reference statements)
0
8
0
Order By: Relevance
“…Viral vectors and non-viral vectors are two main approaches used for siRNA or gene transfer in ocular applications [17,18]. The most used viral vectors for retinal gene transfer are those derived from adenoviruses, lentiviruses and adeno-associated viruses, which can infect and transduce non-dividing cells, such as photoreceptors and the retinal pigment epithelium (RPE) [12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Viral vectors and non-viral vectors are two main approaches used for siRNA or gene transfer in ocular applications [17,18]. The most used viral vectors for retinal gene transfer are those derived from adenoviruses, lentiviruses and adeno-associated viruses, which can infect and transduce non-dividing cells, such as photoreceptors and the retinal pigment epithelium (RPE) [12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…adeno-associated virus (AAV) and lentivirus, are highly effective transfection tools for gene therapy in ophthalmic research. However, this type of delivery vehicle has underlying safety concerns of immunogenicity, broad tissue tropism, carcinogenesis, and genomic insertional mutagenesis in clinical trials, thus in the end it is hoped that physicians and patients will accept only non-viral vectors as the standard of treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent methodologies extend the lifetime of implantable devices by minimizing the adsorption of nonspecific plasma proteins at the initial stage of implantation. ,, Often, the surfaces are functionalized with self-assembled zwitterionic molecules, which form a tightly solvated layer of water molecules, , to impart antifouling capabilities. Compared to conventional hydrophilic polymers, such as polyethylene glycol, many recently developed zwitterionic surfaces exhibit superior performance in resisting protein fouling. ,, Early work by Jiang and co-workers has demonstrated the feasibility of using carboxybetaine and sulfobetaine for zwitterionic antifouling materials. Chen et al have reported ultralow protein adsorption (<0.3 ng/cm 2 ) on surfaces functionalized with a layer of alternating Glu/Lys or Asp/Lys . Moreover, the antifouling properties and long blood circulation characteristics of zwitterions have been integrated recently with quantum dots, hydrogels, silica nanoparticles, , and liposomes to improve functionality across a range of biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…29−31 Chen et al have reported ultralow protein adsorption (<0.3 ng/cm 2 ) on surfaces functionalized with a layer of alternating Glu/Lys or Asp/Lys. 28 Moreover, the antifouling properties and long blood circulation characteristics of zwitterions have been integrated recently with quantum dots, 32 hydrogels, 33 silica nanoparticles, 34,35 and liposomes 36 to improve functionality across a range of biological applications.…”
Section: ■ Introductionmentioning
confidence: 99%